Pengembangan Aplikasi Pembukuan Praktis Untuk UMKM Berbasis Software as a Service Menggunakan Metode Prototype - Gufron (STMIK Budi Darma, 2024)
Financial bookkeeping in a business activity is extremely important. With proper bookkeeping, business owners can monitor cash flow and create financial reports more easily and promptly, thereby helping and facilitating the development of their business into a more professional creative industry. However, many business owners face challenges in creating financial bookkeeping. The main issue is the knowledge of how to prepare accurate and proper financial reports. Additionally, business owners consider focusing on their business activities to be better than learning or creating financial bookkeeping. The purpose of this research is to produce an application that can assist micro, small, and medium enterprises in creating bookkeeping reports. The application development uses a Software as a Service (SaaS) approach because it offers several advantages for users, especially in terms of accessibility and cost. A SaaS-based application allows users to access the bookkeeping system anytime and anywhere as long as they have an internet connection. Furthermore, the SaaS model can reduce the cost burden required for purchasing software licenses. A prototype is used as the method for developing the application because it is one of the strategic steps in supporting the growth of micro, small, and medium businesses. With the increasing need for efficient digital solutions by MSMEs, the SaaS-based bookkeeping application produced in this research can provide ease in financial management, transaction recording, and financial reporting. In this context, the use of the prototype method allows developers and business owners to collaboratively build a purpose-built solution tailored to the specific needs of end users.